High HPgV replication is associated with improved surrogate markers of HIV progression. - Gibran Horemheb-Rubio; Pilar Ramos-Cervantes; Hugo Arroyo-Figueroa; Santiago Ávila-Ríos; Claudia García-Morales; Gustavo Reyes-Terán; Galileo Escobedo; Gloria Estrada; Trinidad García-Iglesias; Nayeli Muñoz-Saucedo; David Kershenobich; Patricia Ostrosky-Wegman; et al. (PLoS ONE)
Background Human Pegivirus (HPgV) may have a beneficial effect on HIV disease progression in co-infected patients; however, the virologic characteristics of this infection are not well defined. In this study, we determined HPgV viremia prevalence in Mexico and provide new insights to understand HPgV infection and HPgV/HIV co-infection. Methods We analyzed and quantified 7,890 serum samples for HPgV viremia by One-Step RT-Real-Time PCR, 6,484 from healthy blood donors and 1,406 from HIV-infected patients. Data on HIV progression were obtained from patients' records. HPgV genotyping was performed in 445 samples by nested PCR of the 5'URT region. Finite Mixture Models were used to identify clustering patterns of HPgV viremia in blood donors and co-infected antiretroviral (ART)-naïve patients. Results HPgV was detected in 2.98% of blood donors and 33% of HIV patients, with a wide range of viral loads. The most prevalent genotypes were 3 (58.6%)and 2 (33.7%). HPgV viral loads from healthy blood donors and HPgV/HIV+ ART-naïve co-infected patients were clustered into two component distributions, low and high, with a cut-off point of 5.07log10 and 5.06log10, respectively. High HPgV viremia was associated with improved surrogate markers of HIV infection, independent of the estimated duration of HIV infection or HIV treatment. Conclusions HPgV prevalence in Mexico was similar to that reported for other countries. The prevalent genotypes could be related to Mexico's geographic location and ethnicity, since genotype 2 is frequent in the United States and Europe and genotype 3 in Asia and Amerindian populations. HPgV viral load demonstrated two patterns of replication, low and high. The more pronounced beneficial response observed in co-infected patients with high HPgV viremia may explain discrepancies found between other studies. Mechanisms explaining high and low HPgV replication should be explored to determine whether the persistently elevated replication depends on host or viral factors.